Chile: Pioneering the protection of neurorights - Lorena Guzmán H. (The UNESCO Courier, 2022)
In 2021, Chile’s Senate unanimously approved a bill to amend the constitution to protect brain rights or “neurorights”. The Chamber of Deputies reviewed and approved the amendment in September that year. It is now expected that the bill will be signed into law by the country’s president.